2005
DOI: 10.1007/bf03218480
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial shear strength and thermal properties of electron beam-treated henequen fibers reinforced unsaturated polyester composites

Abstract: Natural fiber henequen/unsaturated polyester (UPE) composites were fabricated by means of a compression molding technique using chopped henequen fibers treated at various electron beam (EB) dosages. The interfacial shear strength (IFSS), dynamic mechanical properties, and thermal expansion behavior were investigated through a single fiber microbonding test, fractographic observation, dynamic mechanical analysis, and thermomechanical analysis, respectively. The results indicated that the interfacial and dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…For the (120, 1.0, 1.018) treated fiber, the load-displacement curve depicts better bonded interphase; after the interphase has failed, the fiber can still be extracted in a controlled way and friction was measured until the fiber was completely pulled-out. This behavior suggests a better fiber-matrix interlocking and to the possible interaction between the hydrocarbon film deposited onto the surface with the HDPE matrix [11,[14][15][16][18][19][20]. Henequen fibers are polar hydrophilic lignocellulosic fibers because they have a chemical composition consisting of cellulose (70% w/w), hemicellulose (20% w/w), lignin (8%) and extractives (2%).…”
Section: Interfacial Shear Strength Test (Pull Out Test) Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the (120, 1.0, 1.018) treated fiber, the load-displacement curve depicts better bonded interphase; after the interphase has failed, the fiber can still be extracted in a controlled way and friction was measured until the fiber was completely pulled-out. This behavior suggests a better fiber-matrix interlocking and to the possible interaction between the hydrocarbon film deposited onto the surface with the HDPE matrix [11,[14][15][16][18][19][20]. Henequen fibers are polar hydrophilic lignocellulosic fibers because they have a chemical composition consisting of cellulose (70% w/w), hemicellulose (20% w/w), lignin (8%) and extractives (2%).…”
Section: Interfacial Shear Strength Test (Pull Out Test) Resultsmentioning
confidence: 99%
“…However, even though the wet chemical treatments of fiber surfaces have been somewhat successful in improving the interfacial bonding, there are still problems related to the appropriate handling and disposal of the large amounts of hazardous chemicals that are often involved and concerned with environmental pollution problems. These problems have limited a wider industrial application of chemical fiber surface treatments [4,[16][17][18][19][20]. Cold plasma is a solvent-free technique with no liquid waste generated and can therefore be considered as an environmentally sound method.…”
mentioning
confidence: 99%
“…19,20 Figure 7(a) shows the temperature dependence of the storage modulus (E') for unfilled PP and for the non-coupled composites. In all the systems it can be verified that the storage modulus drops upon increasing temperature due to the increased segmental mobility of the polymer chains with heating.…”
Section: Resultsmentioning
confidence: 99%
“…The adhesion between the fibers and matrix was largely enhanced by the PETI-5 interphase. For evaluating the fiber-matrix adhesion of fiberreinforced plastics, interfacial shear strength and/or interlaminar shear strength (ILSS) tests can often provide very useful information [60][61][62]. Short-beam shear test results have indicated that when PETI-5 was sized at 150°C, the ILSS of a 2-directional carbon/BMI composite was markedly improved, by about 35% and 66%, respectively, in comparison to an unsized counterpart, as seen in Fig.…”
Section: Improvement In Adhesion Of Carbon Fiber/ Bmi Composites Usinmentioning
confidence: 99%